Bone mesenchymal stem cells stimulation by magnetic nanoparticles and a static magnetic field: release of exosomal miR-1260a improves osteogenesis and angiogenesis - Wu, Di; Chang, Xiao; Tian, Jingjing; Kang, Lin; Wu, Yuanhao; Liu, Jieying; Wu, Xiangdong; Huang, Yue; Gao, Bo; Wang, Hai; Qiu, Guixing; Wu, Zhihong (Journal of nanobiotechnology, 2021)
The therapeutic potential of exosomes derived from stem cells has attracted increasing interest recently, because they can exert similar paracrine functions of stem cells and overcome the limitations of stem cells transplantation. Exosomes derived from bone mesenchymal stem cells (BMSC-Exos) have been confirmed to promote osteogenesis and angiogenesis. The magnetic nanoparticles (eg. Fe O , γ-Fe O ) combined with a static magnetic field (SMF) has been commonly used to increase wound healing and bone regeneration. Hence, this study aims to evaluate whether exosomes derived from BMSCs preconditioned with a low dose of Fe O nanoparticles with or without the SMF, exert superior pro-osteogenic and pro-angiogenic activities in bone regeneration and the underlying mechanisms involved. Two novel types of exosomes derived from preconditioned BMSCs that fabricated by regulating the contents with the stimulation of magnetic nanoparticles and/or a SMF. Then, the new exosomes were isolated by ultracentrifugation and characterized. Afterwards, we conducted in vitro experiments in which we measured osteogenic differentiation, cell proliferation, cell migration, and tube formation, then established an in vivo critical-sized calvarial defect rat model. The miRNA expression profiles were compared among the exosomes to detect the potential mechanism of improving osteogenesis and angiogenesis. At last, the function of exosomal miRNA during bone regeneration was confirmed by utilizing a series of gain- and loss-of-function experiments in vitro. 50 µg/mL Fe O nanoparticles and a 100 mT SMF were chosen as the optimum magnetic conditions to fabricate two new exosomes, named BMSC-Fe O -Exos and BMSC-Fe O -SMF-Exos. They were both confirmed to enhance osteogenesis and angiogenesis in vitro and in vivo compared with BMSC-Exos, and BMSC-Fe O -SMF-Exos had the most marked effect. The promotion effect was found to be related to the highly riched miR-1260a in BMSC-Fe O -SMF-Exos. Furthermore, miR-1260a was verified to enhance osteogenesis and angiogenesis through inhibition of HDAC7 and COL4A2, respectively. These results suggest that low doses of Fe O nanoparticles combined with a SMF trigger exosomes to exert enhanced osteogenesis and angiogenesis and that targeting of HDAC7 and COL4A2 by exosomal miR-1260a plays a crucial role in this process. This work could provide a new protocol to promote bone regeneration for tissue engineering in the future.